Development of an Environment-Based Critical Thinking Skills Test Instrument for Class VII Middle School Science Learning - Ayuana Kartika Dewi; Baskoro Adi Prayitno; Lina Mahardiani (Jurnal Penelitian Pendidikan IPA, 2024)
This research developed an environment-based critical thinking skills test instrument for science learning in class VII middle school to answer the problem of students' low critical thinking skills in Indonesia. The aim of the research is to produce a valid and reliable instrument to measure students' critical thinking skills in an environmental context. The research method uses the ADDIE development model with a pre-experimental design (one group pretest-posttest). Research findings show that the instrument developed has high validity and reliability and is able to significantly improve students' critical thinking skills. The conclusion of this research is that environment-based test instruments are effective in measuring and improving students' critical thinking skills. The implications of this research show the importance of integrating environmental issues in learning modules to improve the quality of science education in Indonesia.